Primary tumor site is a useful predictor of cetuximab efficacy in the third-line or salvage treatment of KRAS wild-type (exon 2 non-mutant) metastatic colorectal cancer: a nationwide cohort study. Issue 1 (December 2016) - Chen, Kuo-Hsing; Shao, Yu-Yun; Chen, Ho-Min; Lin, Yu-Lin; Lin, Zhong-Zhe; Lai, Mei-Shu; Cheng, Ann-Lii; Yeh, Kun-Huei
Abstract Background Previous studies have shown left-sided colorectal cancer (LCRC) and right-sided colorectal cancer (RCRC) exhibit different molecular and clinicopathological features. We explored the association between the primary tumor site and cetuximab efficacy inKRAS wild-type colorectal cancer (CRC). Methods This study enrolled a cohort of patients, who had received cetuximab treatment after two or more lines of chemotherapy forKRAS wild-type (exon 2 nonmutant) metastatic CRC, from the databases of Taiwan Cancer Registry (2004–2010) and National Health Insurance (2004–2011). Survival data were obtained from the National Death Registry. Time to treatment discontinuation (TTD) and overall survival (OS) after the start of cetuximab treatment were compared between patients with LCRC (splenic flexure to rectum) and RCRC (cecum to hepatic flexure). Results A total of 969 CRC patients were enrolled. Among them, 765 (78.9 %) and 136 (14.0 %) patients had LCRC and RCRC, respectively. Patients with LCRC, compared to patients with RCRC, had longer TTD (median, 4.59 vs. 2.75 months, P  = .0005) and OS (median, 12.62 vs. 8.07 months, P  < .0001) after the start of cetuximab treatment. Multivariate analysis revealed a right-sided primary tumor site was an independent predictor of shorter TTD (adjusted hazard ratio [HR] = 1.32, using the LCRC group as a reference, 95 % confidence interval: 1.08–1.61, P  = .0072) and OS (adjusted HR = 1.45, 95 % CI: 1.18–1.78, P  = .0003). Conclusion Our findings demonstrate that a left-sided primary tumor site is a useful predictor of improved cetuximab efficacy in the third-line or salvage treatment ofKRAS wild-type (exon 2 nonmutant) metastatic CRC.